PENGARUH EKSTRAK DAUN CENGKEH (SYZYGIUM AROMATICUM) PADA DIFFUSER INSECT REPPELENT TERHADAP KEPADATAN LALAT DI TEMPAT PENGOLAHAN TELUR PT.X (Politeknik Kesehatan Kemenkes Bandung, 2021)
Flies are a group of insect that thrive and live in dirty places and play a role in the spread of diseases such as dysentery, cholera, typhoid, diarrhea and other diseases. The purpose of this study was to determine the effect of the concentration of clove leaf extract on the insect reppelent diffuser on the density of flies in the egg processing site of PT.X. This type of research is an experimental research design with pretest posttest without control. the sample in this study were flies in the egg processing area at PT.X. The sample technique is incidental sample. The treatments given were three treatmenta, namely concentration variations of 10%, 15%, and 20%. Observatonal were analyzed using the one way ANOVA test. The postest result showed that there was a significant relationship in the concentration of clove leaf extract and the density of flies at PT.X egg processing site. The result of the measurement of the number of flies that were rejeted with clove leaf extract at a concentration of 10% were 5 brids, a concentration of 15% wa 9 birds and a concenration of 20% wa 17 birds. Based on the research, the concentration that can resist the presence of flies is at a concentration of 20%. It is necessary to develop further research by increasing the concentration to a higher concentration and designing a larger device so that more steam is released and spreads out.